3D-Printed Biopolymers for Tissue Engineering Application. (24th April 2014) - Li, Xiaoming; Cui, Rongrong; Sun, Lianwen; Aifantis, Katerina E.; Fan, Yubo; Feng, Qingling; Cui, Fuzhai; Watari, Fumio
Abstract : 3D printing technology has recently gained substantial interest for potential applications in tissue engineering due to the ability of making a three-dimensional object of virtually any shape from a digital model. 3D-printed biopolymers, which combine the 3D printing technology and biopolymers, have shown great potential in tissue engineering applications and are receiving significant attention, which has resulted in the development of numerous research programs regarding the material systems which are available for 3D printing. This review focuses on recent advances in the development of biopolymer materials, including natural biopolymer-based materials and synthetic biopolymer-based materials prepared using 3D printing technology, and some future challenges and applications of this technology are discussed.